2012
DOI: 10.1002/cbdv.201100264
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Diversity of Volatiles of Teucrium orientale L. var. orientale, var. puberulens, and var. glabrescens Determined by Simultaneous GC‐FID and GC/MS Techniques

Abstract: In the present work, three varieties of Teucrium orientale, var. orientale, var. puberulens, and var. glabrescens, were collected and investigated for chemical composition of the oils. Subsequent gas chromatography (GC-FID) and gas chromatography coupled to mass spectrometry (GC/MS) revealed high abundance of sesquiterpenes in the essential oils analyzed. All the oils contained β-caryophyllene (22.6, 8.5, and 6.3%, resp.) and hexadecanoic acid (7.9, 12.8, and 13.1%). Germacrene D (24.6 and 33.4%) and bicycloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Ozek et al . () reported the presence of 67 compounds representing 96.8% of the oil detected, with a particularly high level of sesquiterpenes (78.7%), in Teucrium orientale L. var. glabrescens .…”
Section: Resultsmentioning
confidence: 99%
“…Ozek et al . () reported the presence of 67 compounds representing 96.8% of the oil detected, with a particularly high level of sesquiterpenes (78.7%), in Teucrium orientale L. var. glabrescens .…”
Section: Resultsmentioning
confidence: 99%
“…Isolated compounds identified in T. lucidum extract are presented in figure 5. The 1 H-NMR spectra highlighted one major compound: it corresponds to Troponin, a neo-clerodane diterpene already identified in an ethanolic extract of aerial parts of T. japonicum [56] , referred to as compound 36. This compound could not be quantified by external standard calibration, and its bioactivities were not assessed as the standard was not available.…”
Section: Compounds Isolation By Semi-preparative Hplc and Nmr Charact...mentioning
confidence: 97%
“…Among them, one molecule is characterised by m/z 377.1219 [M+H] + and m/z 375.2746 [M-H] -and is therefore consistent with the formula C19H20O8.The two other compounds also observed in positive mode are characterised by m/z 361.1271 (ESI+) and m/z 359.1128 (ESI-). They could correspond to isomers characterised by the MF C19H20O7.The 1 H-NMR spectra highlighted one major compound: it corresponds to Troponin, a neo-clerodane diterpene already identified in an ethanolic extract of aerial parts of T. japonicum[56] , referred to as compound 36. This compound could not be quantified by external standard calibration, and its bioactivities were not assessed as the standard was not available.The major compound of fraction TL_FR4, eluting at 42 min in HPLC-DAD-ELSD, is characterised by a protonated molecule at m/z 329 [M+H]+ and a fragment at m/z 311 [M+H-H 2 O]+.…”
mentioning
confidence: 94%
“…%; calculated from the FID chromatograms. RRI b : RRI from literature (c [ 63 ], d [ 64 ], e [ 65 ], f [ 23 ], g [ 66 ], h [ 67 ], k [ 68 ]) for polar column values; tr; Trace (<0.1 %). Identification method (IM): t R , identification based on the retention times (t R ) of genuine compounds on the HP Innowax column; MS, identified on the basis of computer matching of the mass spectra with those of the in-house Baser Library of Essential Oil Constituents, Adams, MassFinder and Wiley libraries and comparison with literature data.…”
Section: Figurementioning
confidence: 99%
“…However, recent experiments have shown that these compounds may also have toxic effects [19]. Considering the diversity of major compounds, the essential oil composition of Teucrium was primarily characterized with mono and sesquiterpenes such as α-pinene, β-pinene, caryophyllene oxide, β-caryophyllene, germacrene D, and bicyclogermacrene [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%